Abdominal Tuberculosis in Nepal Medical College Teaching Hospital, Kathmandu (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Abdominal Tuberculosis is a common extra pulmonary manifestation of tuberculosis. The wide spectrum of presentation makes abdominal tuberculosis difficult to diagnose and treat. Retrospective review of cases with abdominal tuberculosis presenting to the Surgery Department of Nepal Medical College Teaching Hospital from January 2002- June 2007 was done to describe our experience of abdominal tuberculosis over a 5 year period. We found total 32 patients with abdominal tuberculosis, among which 13 had concurrent pulmonary tuberculosis. The most common clinical presentation, i.e. a triad of abdominal pain, fever and weight loss was present in 13 who had symptoms of pulmonary tuberculosis presented to physicians and the remaining 19 presented acutely to surgeons with symptoms of pain and obstruction. Chest X ray, abdominal ultrasound and barium meal follow through done to find associated abnormalities. Diagnostic Laparoscopy was performed in 10 and 3 patients with peritonitis underwent emergency laparotomy which revealed multiple ileal perforations in 2 cases and one had multiple strictures with small bowel perforation. Diagnosis of tuberculosis, attended at surgeons was confirmed by demonstrating caseating granulomas in histology and Acid Fast Bacilli Positive, culture for M. tuberculosis from peritoneal fluid. All patients were started anti tuberculosis treatment. Abdominal tuberculosis is a relatively common finding and should always be considered in the differential diagnosis of abdominal pain, fever and weight loss. Key Words: Tuberculosis; abdominal tuberculosis; Acid Fast Bacilli; ileocaecal disease DOI: 10.3126/saarctb.v5i1.3083 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(1) 39-42